2020
DOI: 10.1166/jnn.2020.17397
|View full text |Cite
|
Sign up to set email alerts
|

Morphology Dependent Photocatalytic Activity of CuO/CuO–TiO2 Nanocatalyst for Degradation of Methyl Orange Under Sunlight

Abstract: CuO nanoparticles have been extensively used as a photocatalyst because of their superior activity, selectivity and stability properties. The catalytic efficiency of these oxide nanoparticles can be improved by varying the size and shape of nanoparticles. Here, we report the synthesis of different shaped CuO nanoparticles and their impregnation on TiO2. Optical analysis revealed that a considerable red shift (420 nm to 550 nm) in absorption spectra of CuO–TiO2 nanocomposites was observed compared to bare CuO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…A large number of studies have proved that nanoscale spherical TiO 2 shows excellent performance in photocatalytic degradation of dyeing wastewater and has been widely used. In the experimental study, typical dyes such as RhB, [ 209 ] MO, [ 210 ] and MB [ 211 ] are usually used as the object of degradation. Yan [ 212 ] et al.…”
Section: Application Of Nanoscale Spherical Tio2 In Photocatalytic Dementioning
confidence: 99%
“…A large number of studies have proved that nanoscale spherical TiO 2 shows excellent performance in photocatalytic degradation of dyeing wastewater and has been widely used. In the experimental study, typical dyes such as RhB, [ 209 ] MO, [ 210 ] and MB [ 211 ] are usually used as the object of degradation. Yan [ 212 ] et al.…”
Section: Application Of Nanoscale Spherical Tio2 In Photocatalytic Dementioning
confidence: 99%
“…The average hydrodynamic diameter (intensity) ofthe compound 1 was ~107.1 nm, and compound 2 was ~108.0 nm( Figure 2B). There is, however, a certain adhesionbetween nanoparticles formed by the self-assembly of simplesmall-molecule drugs [51][52][53]. Therefore, we have a miscible liquidwith many hydrophobic drugs by combining the prodrug with theappropriate amount of C225 molecules.…”
Section: Characterization Of C-au-pfh-npsmentioning
confidence: 99%
“…It is believed that this superiority was mainly due to the suitability of the size of the methyl orange molecule with the pore size of TiO2. Meanwhile, Bathla and co-workers also utilized CuO-TiO2 material with several morphological forms of TiO2, such as stars, needles, and crumbles [62]. Based on the result, it was found that CuO-TiO2 nanostars have the highest photodegradation efficiency with a reaction time of 480 minutes.…”
Section: Methyl Orangementioning
confidence: 99%